Technology Roadmap for Small Modular Reactor Deployment. (IAEA nuclear energy series, 2021)
"Technology roadmaps have proven to be a useful management tool for evaluating, planning and strategizing the development of complex technological projects. This publication is intended to provide Member States with a set of generic roadmaps which can be used in the deployment of small modular reactors. These roadmaps are based on the latest inputs from Member States currently pursuing this technology. The publication places emphasis on the activities of owners/operators who drive the demand and requirements for the reactor designs, the designers who develop the technologies, and the regulators who establish and maintain the regulatory requirements that owners/operators should meet. It also provides a methodology for developing a technology roadmap for reactors with longer development horizons and discusses emerging opportunities and challenges for this relatively new technology."--Publisher's description.